Rechssttaat and Rule of Law: Some Aspects - TEMIRBEKOV, Zhalgas; ZHUSSUPOV, Alpysbay; ORAZBAYEVA, Aliya; SULEIMENOVA, Dina; OMAROVA, Raushan (Journal of Advanced Research in Law and Economics, 2017)
Concepts of the Rule of law and Rechtsstaat reflect the general tendency of recognizing law priority in various legal doctrines and different legal systems. The concept of the Rule of law focuses on more broad meaning of law and its genetic fundamental priority in relation to the state contains a significant non-state element. The interpretation of the state includes sharing the power and obligations between various institutes representing ‘the different authorities’ for their self-control including law making, interpretation of law and its application is the cornerstone of Rechtsstaat. The interpretation of Rechtsstaat in theoretical concepts is allied to the sociological and psychological schools of law and more affined to the concept of the Rule of law. Despite distinction in an origin, concepts of the Rule of law and Rechtsstaat have similar objectives – the seeking of an ideal of legitimacy of the government and to support the optimum regime of rights and freedoms of subjects of law, which is necessary for harmonious and stable development of the society.